Analysis of The Economic Gap The Community of Citraland Surabaya and The Surrounding Region (NeoRespublica : Jurnal Ilmu Pemerintahan, 2022)
One of the satellite cities in Surabaya is Citraland which has been established since 1993 as one of the largest real estate companies in Surabaya. The development of satellite cities which are synonymous with luxury housing has had its own impact, namely there has been a gap with the surrounding area. region and economic disparity (Adisasmita, 2005). Basically housing construction has an impact on economic disparities in the surrounding community. In addition, it also creates an increasingly widening welfare gap between low and high income groups which is measured by income inequality. The method used in this research is literature study. The results of this study are three factors that cause economic inequality, namely first, there is a high disparity related to the income of rural communities and housing; second, there are differences in daily lifestyles; third, differences in geographical conditions/environment of residence.